Negative electrode material and preparation method and application thereof
By using a core-shell structure negative electrode material coated with titanium dioxide with copper oxide, the problems of low rate performance and poor conductivity in high-capacity lithium-ion batteries are solved, and the performance of lithium-ion batteries with high conductivity and high energy density are achieved.
Patent Information
- Application Number
- CN202411823103.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-10
- Publication Date
- 2025-03-18
AI Technical Summary
Traditional graphite anode materials have low magnification performance and low lithium embedded potential in high-capacity lithium-ion batteries, making it difficult to meet the needs of high energy density. The theoretical specific capacity of titanium dioxide anode materials is low and have poor ion and electron conductivity, which limits their application.
The core-shell structure negative electrode material of copper oxide coated with titanium dioxide is used to synthesize a composite material of titanium dioxide core and cuprous oxide coating layer to improve the conductivity and cyclic properties of the material.
It achieves high conductivity, high rate performance and good cycle performance, and improves the overall performance of lithium-ion batteries, especially energy density and cycle stability.
Smart Images

Figure BDA0005184012250000101 
Figure HDA0005184012320000011 
Figure HDA0005184012320000012
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of lithium ion batteries, and more specifically, to a negative electrode material and a preparation method thereof. Background Art
[0002] As the global demand for clean energy and sustainable development continues to grow, lithium-ion batteries have been increasingly widely used in many fields such as mobile electronic devices, electric vehicles, and large-scale energy storage due to their high energy density and stable cycle performance. As one of the key components of lithium-ion batteries, the performance of negative electrode materials directly affects the overall performance of the battery. Therefore, the research on negative electrode materials for lithium batteries has important practical significance.
[0003] Traditional negative electrode materials use graphite, which has low rate performance and low lithium insertion potential, making it difficult to meet the needs of high-capacity batteries. In view of this, current research on negative electrode materials for lithium-ion batteries is mainly focused on non-carbon negative electrode materials, such as iron oxide, titanium dioxide, nickel oxide, molybdenum disulfide, and cuprous oxide. Among them, titanium dioxide has a high lithium insertion potential, abundant reserves, is non-toxic and harmless, has a high discharge potential, and has a small volume expansion during lithium ion insertion and extraction. It is considered to be a potential negative electrode material. However, TiO 2 There are also some limitations in the practical application of negative electrode materials in lithium-ion batteries, such as low theoretical specific capacity (335mAh·g -1 ), poor ion and electron conductivity, which hinder its further application and development. Summary of the invention
[0004] In view of this, the object of the present invention is to provide a negative electrode material and a preparation method and application thereof. The negative electrode material provided by the present invention adopts a core-shell structure of cuprous oxide coated with titanium dioxide, and has high conductivity, high rate performance and good cycle performance.
[0005] The invention provides a negative electrode material with a core-shell structure, comprising a titanium dioxide core and a coating layer composited on the surface of the titanium dioxide core; the coating layer is composed of cuprous oxide particles.
[0006] Preferably, the particle size of the titanium dioxide core is 50nm to 100nm; the thickness of the coating layer is 15nm to 20nm.
[0007] The present invention also provides a method for preparing the negative electrode material described in the above technical solution, comprising the following steps:
[0008] a) Titanium dioxide, CuCl 2 ·2H 2 O, a base, water and a reducing agent are mixed to react to obtain a reaction mixture;
[0009] b) The reaction mixture obtained in step a) is sequentially cooled, centrifuged and dried to obtain a negative electrode material.
[0010] Preferably, the preparation method of titanium dioxide in step a) is specifically as follows:
[0011] The titanium source and anhydrous ethanol are mixed and sealed in a high-pressure reactor, and placed in a vacuum oven at 120° C. to 220° C. for reaction for 20 h to 30 h; the reaction mixture is then cooled, separated and dried in sequence to obtain titanium dioxide.
[0012] Preferably, the titanium dioxide and CuCl in step a) 2 ·2H 2 The mass ratio of O is (1~4):1.
[0013] Preferably, in step a), the base is selected from potassium hydroxide and / or sodium hydroxide; and the reducing agent is selected from glucose and / or ascorbic acid.
[0014] Preferably, in step a), the CuCl 2 ·2H 2 The mass ratio of O to alkali, water and reducing agent is 1:(1.5-4):(20-200):(0.3-1.5).
[0015] Preferably, the reaction temperature in step a) is 50° C. to 110° C., the rotation speed is 500 rpm to 800 rpm, and the reaction time is 1 h to 3 h.
[0016] Preferably, in step b), the cooling temperature is 20°C to 30°C, the centrifugal separation speed is 7500rpm to 11000rpm, and the time is 5min to 20min; the drying temperature is 60°C to 85°C, and the time is 10h to 30h.
[0017] The present invention also provides a lithium-ion battery, comprising: a negative electrode plate, a positive electrode plate, a separator and an electrolyte, wherein the negative electrode plate comprises the negative electrode material described in the above technical solution.
[0018] The present invention provides a negative electrode material and a preparation method and application thereof; the negative electrode material has a core-shell structure, including a titanium dioxide core and a coating layer composited on the surface of the titanium dioxide core; the coating layer is composed of cuprous oxide particles; the preparation method of the negative electrode material comprises the following steps: a) titanium dioxide, CuCl 2 ·2H 2O, alkali, water and a reducing agent are mixed and reacted to obtain a reaction mixture; b) the reaction mixture obtained in step a) is sequentially cooled, centrifuged and dried to obtain a negative electrode material. Compared with the prior art, the negative electrode material provided by the present invention adopts a core-shell structure of cuprous oxide coated with titanium dioxide, which achieves better overall interaction, can improve the coating-foil interface, and form an interface effect of an "electronic highway network", thereby improving the material conductivity, rate performance and cycle performance.
[0019] At the same time, the preparation method provided by the present invention has simple process, mild conditions, easy control, high preparation efficiency, low cost, and broad application prospects. BRIEF DESCRIPTION OF THE DRAWINGS
[0020] Figure 1 A flow chart of a method for preparing a negative electrode material provided in Example 1 of the present invention;
[0021] Figure 2 Schematic diagram of the movement of electrons and lithium ions inside the electrode during discharge (left) and charge (right) in Example 1 of the present invention;
[0022] Figure 3 This is a SEM image of the material in Example 1 of the present invention;
[0023] Figure 4 This is the XRD diagram of the material in Example 1 of the present invention. DETAILED DESCRIPTION
[0024] The technical solution of the present invention will be clearly and completely described below in conjunction with the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0025] The invention provides a negative electrode material with a core-shell structure, comprising a titanium dioxide core and a coating layer composited on the surface of the titanium dioxide core; the coating layer is composed of cuprous oxide particles.
[0026] In recent years, the research on metal oxides as coating carriers has attracted more and more attention. 2 O) is an ideal negative electrode material for lithium batteries due to its high theoretical specific capacity (674 mAh g -1 ), short electron / ion diffusion paths, and Cu 2The advantages of the O / Cu interface, such as good conductivity, have attracted wide attention. On this basis, in order to fully improve the conductivity of the material, improve the rate performance and cycle performance, the present invention synthesizes a lithium-ion battery negative electrode material of cuprous oxide coated with titanium dioxide; the material forms an interface effect with the negative electrode sheet, forming an "electronic highway network", thereby improving the conductivity of the material.
[0027] In the present invention, the negative electrode material has a core-shell structure, including a titanium dioxide core and a coating layer composited on the surface of the titanium dioxide core, preferably consisting of a titanium dioxide core and a coating layer composited on the surface of the titanium dioxide core.
[0028] In the present invention, the coating layer is composed of cuprous oxide particles.
[0029] In the present invention, the particle size of the titanium dioxide core is preferably 50 nm to 100 nm; the thickness of the coating layer is preferably 15 nm to 20 nm.
[0030] The negative electrode material provided by the present invention is a lithium ion battery negative electrode material of cuprous oxide coated with titanium dioxide, which is applied to the negative electrode plate and can be 2 -Cu 2 The construction of the O / Cu foil interface forms an electronic highway network, which allows more conductive pathways to be formed at the interface, allowing electrons and ions to be transmitted quickly and non-tortuously at the critical point, optimizing the transmission path, improving the conductivity of the coating and the electrode, and reducing the electron transmission resistance of the electrode, thereby improving the rate performance and cycle performance of the lithium-ion battery; in addition, the above-mentioned interface structure can provide more reaction active sites and improve the energy density of the battery.
[0031] The present invention also provides a method for preparing the negative electrode material described in the above technical solution, comprising the following steps:
[0032] a) Titanium dioxide, CuCl 2 ·2H 2 O, a base, water and a reducing agent are mixed to react to obtain a reaction mixture;
[0033] b) The reaction mixture obtained in step a) is sequentially cooled, centrifuged and dried to obtain a negative electrode material.
[0034] The present invention firstly treats titanium dioxide, CuCl 2 ·2H 2 O, a base, water and a reducing agent are mixed to react to obtain a reaction mixture.
[0035] In the present invention, the titanium dioxide can be titanium dioxide powder from commercial sources or homemade titanium dioxide; the preparation method of the titanium dioxide is preferably as follows:
[0036] The titanium source and anhydrous ethanol are mixed and sealed in a high-pressure reactor, and then placed in a vacuum oven for reaction at 120°C to 220°C for 20h to 30h, preferably at 160°C to 200°C for 24h; then the reaction mixture is cooled (to room temperature), separated and dried in sequence to obtain titanium dioxide; the separation process is preferably as follows: centrifuging at 7500rpm to 10000rpm for 5min to 20min and then separating the product; the drying process is preferably as follows: drying in a vacuum oven at 60°C to 85°C overnight to obtain titanium dioxide.
[0037] In the present invention, the titanium source is preferably selected from titanium isopropoxide (Ti(OCH(CH 3 ) 2 ), titanium tetrachloride, barium metatitanate, titanium sulfate, more preferably titanium isopropoxide (Ti(OCH(CH 3 ) 2 ). The present invention has no special restrictions on the sources of the titanium source and anhydrous ethanol, and commercially available products known to those skilled in the art can be used.
[0038] In a preferred embodiment of the present invention, the titanium source is 0.01 mol / L to 0.05 mol / L titanium isopropoxide in an amount of 2 to 10 ml, which is slowly added to 30 ml to 80 ml of anhydrous ethanol under stirring, and then transferred to a 100 ml or 150 ml high-pressure reactor and sealed.
[0039] In the present invention, the titanium dioxide and CuCl 2 ·2H 2 The mass ratio of O is preferably (1-4):1, specifically 1:1, 2:1, 3:1, 4:1, and more preferably 2:1. In the present invention, the ratio of the reactants will affect the thickness of the coating layer. If the cuprous oxide content is too high, the thickness of the outer coating will be larger, which will hinder the transmission of electrons and increase the internal resistance, thereby affecting the rate and cycle performance of the battery; if the cuprous oxide content is too low, the thickness of the coating layer will be too small, and the interface formed between the negative electrode material and the electrode sheet will be unstable during the cyclic charge and discharge process, which will affect the transmission of electrons and further affect the rate and cycle performance of the battery. A suitable ratio of reactants will generate materials with suitable particle sizes and coating layers, so that a stable interface is formed between the negative electrode material and the foil, thereby accelerating electron transfer, reducing the internal resistance of the battery, and improving the rate performance and cycle performance of the battery. The present invention is directed to the CuCl 2 ·2H 2 The source of O is not particularly limited, and a commercially available product known to those skilled in the art may be used.
[0040] In the present invention, the base is preferably selected from potassium hydroxide and / or sodium hydroxide, more preferably sodium hydroxide; the reducing agent is preferably selected from glucose and / or ascorbic acid, more preferably glucose. The present invention has no particular restrictions on the sources of the base and reducing agent, and commercially available products known to those skilled in the art can be used.
[0041] In the present invention, the CuCl 2 ·2H 2 The mass ratio of O to alkali, water and reducing agent is preferably 1: (1.5-4): (20-200): (0.3-1.5), and more preferably 1: (2-3): (80-120): (0.7-0.8).
[0042] In the present invention, the mixing process is preferably specifically as follows:
[0043] First weigh titanium dioxide and CuCl 2 ·2H 2 O(CuCl 2 ·2H 2 The mass of O is fixed, and the mass of titanium dioxide is mainly changed to adjust the mass of titanium dioxide and CuCl 2 ·2H 2 0 ratio) in deionized water, then weigh the alkali and dissolve it in deionized water completely, take the reducing agent and add it to the beaker, then add the aforementioned titanium dioxide, CuCl 2 ·2H 2 The O and base solutions were added to the beaker and mixed using a magnetic stirrer.
[0044] In the present invention, the reaction temperature is preferably 50°C to 110°C, specifically 50°C, 70°C, 90°C, 110°C, the speed is preferably 500rpm to 800rpm, more preferably 600rpm to 700rpm, the time is preferably 1h to 3h, more preferably 2h. In the present invention, the reaction temperature of the reactants will affect the pore size of the material. When the temperature is low (50°C), it will cause CuCl 2 ·2H 2 O and TiO 2 The reaction is incomplete, resulting in copper hydroxide remaining on the TiO 2The surface hinders the transmission of electrons, resulting in an increase in internal resistance, which in turn affects the rate and cycle performance of the battery. When the temperature is high (110°C), the high temperature will cause the prepared material to agglomerate, affecting the porosity of the negative electrode material. The small porosity makes it difficult to embed lithium ions, resulting in a decrease in the energy density of the battery. In addition, the high temperature will cause the material to be inactivated, hinder the transmission of electrons, and increase the internal resistance, which in turn affects the rate and cycle performance of the battery. The appropriate temperature will generate materials with the appropriate particle size, thereby achieving the purpose of accelerating electron transfer, so that the rate performance and cycle performance of the battery are improved.
[0045] In the present invention, the cooling temperature is preferably 20°C to 30°C, the centrifugal separation speed is preferably 7500rpm to 11000rpm, more preferably 9000rpm to 10000rpm, and the time is preferably 5min to 20min, more preferably 10min to 15min.
[0046] In the present invention, the drying process is preferably carried out in a vacuum oven, the drying temperature is preferably 60°C to 85°C, more preferably 65°C to 70°C, and the drying time is preferably 10h to 30h; Cu 2 O / TiO 2 Material.
[0047] The preparation method provided by the invention has simple process, mild conditions, easy control, high preparation efficiency, low cost and broad application prospects.
[0048] The present invention also provides a lithium-ion battery, comprising: a negative electrode plate, a positive electrode plate, a separator and an electrolyte, wherein the negative electrode plate comprises the negative electrode material described in the above technical solution.
[0049] The present invention has no special restrictions on the types and sources of the positive electrode sheet, separator and electrolyte of the lithium ion battery. The positive electrode sheet, separator and electrolyte well known to those skilled in the art for preparing lithium ion batteries can be used.
[0050] In the present invention, the negative electrode sheet includes the negative electrode material described in the above technical solution. In a preferred embodiment of the present invention, the negative electrode sheet is prepared by mixing the negative electrode material, conductive agent, and binder described in the above technical solution in a mass ratio of 71: (1-3): (28-26), stirring them in deionized water at a high speed to obtain a negative electrode slurry, coating it on a conventional copper foil, drying it, and pressing it into a sheet.
[0051] The present invention has no special limitation on the method for preparing the lithium-ion battery, and any technical solution for preparing lithium-ion batteries well known to those skilled in the art may be used.
[0052] The present invention provides a negative electrode material and a preparation method and application thereof, which have the following advantages: (1) TiO 2 -Cu 2 The construction of the TiO / Cu foil interface is beneficial to the transmission of electrons and ions at the interface, improving the conductivity of the coating and the electrode, and reducing the electron transfer resistance of the electrode; (2) The interface structure can reduce the charge transfer resistance, thereby improving the rate performance and cycle performance of lithium-ion batteries; (3) TiO 2 -Cu 2 The construction of O / Cu foil interface can provide more reactive sites and improve the energy density of the battery.
[0053] The present invention provides a negative electrode material and a preparation method and application thereof; the negative electrode material has a core-shell structure, including a titanium dioxide core and a coating layer composited on the surface of the titanium dioxide core; the coating layer is composed of cuprous oxide particles; the preparation method of the negative electrode material comprises the following steps: a) titanium dioxide, CuCl 2 ·2H 2 O, alkali, water and a reducing agent are mixed and reacted to obtain a reaction mixture; b) the reaction mixture obtained in step a) is sequentially cooled, centrifuged and dried to obtain a negative electrode material. Compared with the prior art, the negative electrode material provided by the present invention adopts a core-shell structure of cuprous oxide coated with titanium dioxide, which achieves better overall interaction, can improve the coating-foil interface, and form an interface effect of an "electronic highway network", thereby improving the material conductivity, rate performance and cycle performance.
[0054] At the same time, the preparation method provided by the present invention has simple process, mild conditions, easy control, high preparation efficiency, low cost, and broad application prospects.
[0055] In order to further illustrate the present invention, the following examples are used to explain it in detail. The raw materials used in the following examples of the present invention are all commercially available. Performance evaluation of full batteries: The batteries of the examples and comparative examples are prepared according to the following steps and methods.
[0056] Example: Cu obtained by different reactant preparation temperatures and ratios 2 O / TiO 2 The negative electrode material is used as a negative electrode sheet for the battery.
[0057] Comparative example: TiO 2 And graphite is used as the negative electrode material to make the negative electrode plate.
[0058] Example 1
[0059] 1. Preparation of negative electrode materials (see the overall flow chart) Figure 1 shown):
[0060] (1)TiO 2The synthesis process of the material: First, 0.03 mol / L titanium isopropoxide (Ti(OCH(CH 3 ) 2 ), 5 ml) was slowly added to 50 ml of anhydrous ethanol under stirring. Then it was transferred to a 100 ml autoclave, sealed and kept at 180 ° C for 24 hours. The mixture was then cooled to room temperature and centrifuged at 10000 rpm for 10 minutes to separate the product. The final material was dried in a vacuum oven at 65 ° C overnight to successfully obtain TiO 2 Material.
[0061] (2)Cu 2 O / TiO 2 Material synthesis process: First weigh 2.0g TiO 2 powder with 1.0g CuCl 2 ·2H 2 O was dissolved in 50 ml of deionized water, and then 3.0 g of NaOH was weighed and dissolved in 50 ml of water until it was completely dissolved. 0.77 g of glucose was added to the beaker, and then the TiO 2 , CuCl 2 ·2H 2 O and NaOH solution were added to a beaker, placed in a magnetic stirrer at 90°C and 700 rpm, heated and stirred for 2 hours, then the mixture was cooled to room temperature and centrifuged at 10,000 rpm for 10 minutes to separate the product. The final material was dried in a vacuum oven at 65°C overnight to successfully obtain cuprous oxide-coated titanium dioxide (Cu 2 O / TiO 2 ) of lithium-ion battery negative electrode materials.
[0062] See also Figure 3 and Figure 4 , respectively, the SEM and XRD spectra of the materials. The SEM graph shows that TiO 2 In the core, the outer surface is coated with Cu 2 O shell, XRD crystal surface characteristic peaks prove the successful preparation of Cu 2 O / TiO 2 Material.
[0063] 2. Preparation of negative electrode sheet:
[0064] The prepared negative electrode active material, conductive agent (conductive carbon black) and binder (CMC) are mixed in a mass ratio of 71:2:27 to obtain a mixed material, the mixed material is fully and uniformly stirred at a high speed in deionized water to obtain a negative electrode slurry, the negative electrode slurry is coated on a conventional copper foil, and after drying and pressing, a negative electrode sheet is obtained.
[0065] 3. Preparation of positive electrode sheet:
[0066] The positive electrode active material (lithium iron phosphate material), the conductive agent (conductive carbon black) and the binder (PVDF) are mixed in a mass ratio of 95:4:1 to obtain a mixed material, the mixed material is fully and uniformly stirred in NMP at a high speed to obtain a positive electrode slurry, the positive electrode slurry is coated on a conventional aluminum foil, and after drying and pressing, a positive electrode sheet is obtained.
[0067] 4. Isolation film:
[0068] PP porous polymer film is used as the isolation membrane.
[0069] 5. Electrolyte:
[0070] Ethylene carbonate (EC), dimethyl carbonate (DMC), and diethyl carbonate (DEC) were mixed in a volume ratio of 1:1:1, and then the fully dried lithium salt LiPF 6 It is dissolved in a mixed organic solvent at a ratio of 1 mol / L to prepare an electrolyte.
[0071] 6. Preparation of lithium batteries:
[0072] After weighing, the electrode sheet was directly used as the negative electrode of the lithium-ion battery in a glove box filled with Ar to assemble a 2032-type button battery. The assembly order of the battery from top to bottom is: negative electrode shell, gasket, gasket, lithium sheet, diaphragm, self-supporting electrode sheet, positive electrode shell. The obtained button battery was further tested on a charge and discharge tester. The movement process of electrons and lithium ions inside the electrode sheet during discharge (left) and charge (right) is shown in Figure 2. Figure 2 The synthesized composite negative electrode material was tested for 200 cycles at a current density of 100 mA / g to detect its cycle stability.
[0073] Embodiments 2 to 4
[0074] Preparation of negative electrode materials:
[0075] The preparation conditions in (1) are the same as those in Example 1 to obtain TiO 2 Material.
[0076] The temperature of the magnetic stirrer in (2) was set to 50°C, 70°C, and 110°C, respectively, and the remaining steps were the same as in Example 1 to obtain Cu 2 O / TiO 2 -50, Cu 2 O / TiO 2 -70, Cu 2 O / TiO 2 -110 materials.
[0077] The preparation of the negative electrode sheet, the positive electrode sheet, the separator, the electrolyte and the battery is the same as in Example 1.
[0078] Embodiments 5 to 7
[0079] Preparation of negative electrode materials:
[0080] The preparation conditions in (1) are the same as those in Example 1 to obtain TiO 2 Material.
[0081] The CuCl in (2) 2 ·2H 2 O and TiO 2 The mass ratio of the powder was changed to 1:1, 1:3, 1:4 (CuCl 2 ·2H 2 O mass remains unchanged at 1.0 g, and TiO 2 The mass of the powder was changed to 1.0 g, 3.0 g, and 4.0 g). The temperature of the magnetic stirrer was set to 90 °C to obtain Cu 2 O / TiO 2 -1.Cu 2 O / TiO 2 -2.Cu 2 O / TiO 2 -3.Cu 2 O / TiO 2 -4 Materials.
[0082] The preparation of the negative electrode sheet, the positive electrode sheet, the separator, the electrolyte and the battery is the same as in Example 1.
[0083] Comparative Examples 1-2
[0084] The negative electrode materials are graphite and TiO 2 , TiO 2 The preparation method is the same as that of Example 1. The preparation of the negative electrode sheet, the positive electrode sheet, the separator, the electrolyte and the battery is the same as that of Example 1.
[0085] Electrical performance test:
[0086] (1) Internal resistance test: The internal resistance of different groups of batteries is obtained by a battery internal resistance meter.
[0087] (2) Rate performance test: At 25°C, the battery was charged at a constant current of 0.33C to 3.65V, and then charged at a constant voltage of 3.65V to a current of I≤0.05C. The battery charging capacity was recorded as C0. After standing for 5 minutes, the battery was discharged at a constant current of 0.33C to 2.0V. The battery discharge capacity was recorded as C1. The rate performance was calculated according to C1 / C0×100%.
[0088] (3) Battery energy density test: First weigh the battery and record its weight as m. Then, at 25°C, charge the battery at a constant current of 0.33C to 3.65V. Then, charge it at a constant voltage of 3.65V to a current ≤0.05C. After standing for 5 minutes, discharge it at a constant current of 0.33C to 2.0V. The discharge energy Q is obtained. The battery energy density is calculated as Q / m.
[0089] (4) Battery cycle performance test: At 25°C, charge the battery at a constant current of 0.33C to a voltage of 3.65V, then charge at a constant voltage to a current of 0.05C; after standing for 5 minutes, discharge the battery at a constant current of 0.33C to 2.0V, and record the discharge capacity at this time, which is the discharge capacity of the first cycle C0. Perform a cycle test according to this process, and record the capacity at the 200th cycle. Record it as C, and use the formula C / C0×100% to obtain the capacity retention rate after 200 cycles.
[0090] Table 1 below summarizes the electrical performance test results of the embodiments and comparative examples.
[0091] Table 1
[0092]
[0093]
[0094] According to the test results of the embodiments and comparative examples, the Cu 2 O / TiO 2 The negative electrode sheet made of negative electrode material is better than TiO 2 The internal resistance of the negative electrode sheet made of graphite negative electrode material is significantly reduced, and the energy density is increased by 12.9% and 13.4% respectively, and the battery cycle performance is good. Under the condition of the optimal reactant temperature, the ratio of the reactants is changed, and it is found that when the ratio is moderate (1:2), the internal resistance is small, and the energy density and cycle performance are optimal.
[0095] The above description of the disclosed embodiments enables those skilled in the art to implement or use the present invention. Various modifications to these embodiments will be apparent to those skilled in the art, and the general principles defined herein may be implemented in other embodiments without departing from the spirit or scope of the present invention. Therefore, the present invention will not be limited to the embodiments shown herein, but rather to the widest scope consistent with the principles and novel features disclosed herein.
Claims
1. A negative electrode material, characterized in that: The invention has a core-shell structure, comprising a titanium dioxide core and a coating layer composited on the surface of the titanium dioxide core; the coating layer is composed of cuprous oxide particles.
2. The negative electrode material according to claim 1, characterized in that The particle size of the titanium dioxide core is 50nm-100nm; the thickness of the coating layer is 15nm-20nm.
3. A method for preparing the negative electrode material according to any one of claims 1 to 2, characterized in that: The following steps are involved: a) mixing titanium dioxide, CuCl2·2H2O, alkali, water and a reducing agent to react and obtain a reaction mixture; b) The reaction mixture obtained in step a) is sequentially cooled, centrifuged and dried to obtain a negative electrode material.
4. The preparation method according to claim 3, characterized in that: The preparation method of titanium dioxide in step a) is specifically as follows: The titanium source and anhydrous ethanol are mixed and sealed in a high-pressure reactor, and placed in a vacuum oven at 120° C. to 220° C. for reaction for 20 h to 30 h; the reaction mixture is then cooled, separated and dried in sequence to obtain titanium dioxide.
5. The preparation method according to claim 3, characterized in that: The mass ratio of titanium dioxide to CuCl2·2H2O in step a) is (1-4):
1.
6. The preparation method according to claim 3, characterized in that: In step a), the base is selected from potassium hydroxide and / or sodium hydroxide; the reducing agent is selected from glucose and / or ascorbic acid.
7. The preparation method according to claim 3, characterized in that: The mass ratio of CuCl2·2H2O to alkali, water and reducing agent in step a) is 1:(1.5-4):(20-200):(0.3-1.5).
8. The preparation method according to claim 3, characterized in that: The reaction temperature in step a) is 50° C. to 110° C., the rotation speed is 500 rpm to 800 rpm, and the reaction time is 1 h to 3 h.
9. The preparation method according to claim 3, characterized in that: In step b), the cooling temperature is 20°C to 30°C, the centrifugal separation speed is 7500rpm to 11000rpm, and the time is 5min to 20min; the drying temperature is 60°C to 85°C, and the time is 10h to 30h.
10. A lithium ion battery comprising: A negative electrode sheet, a positive electrode sheet, a separator and an electrolyte, wherein the negative electrode sheet comprises the negative electrode material according to any one of claims 1 to 2.
Citation Information
Patent Citations
Functional nano Ti2O / Cu2O heterophase Fenton thin film and preparation method as well as use
CN101322939A
Lithium ion battery negative electrode material and preparation method thereof
CN107732172A
Titanium dioxide-copper oxide nano compound and preparation method and application thereof
CN107799744A
Lithium-ion battery negative electrode material and preparation method thereof, lithium-ion battery negative electrode and lithium-ion battery
CN111129441A
Porous titanium dioxide-cuprous oxide composite material as well as preparation method and application thereof
CN113694925A